TANGGUNG JAWAB PENGUSAHA PARIWISATA TERHADAP KESELAMATAN WISATAWAN BUKIT SELANCANG, DESA AUR CINA BERDASARKAN UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN - Nadia Sanjaya; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Article 20 of Law Number 10 of 2009 concerning Tourism states that everytourist has the right to obtain accurate information about tourist attractions,tourism services that meet standards, legal and security protection, health services,protection of personal rights, and insurance protection against risks. . tourismactivities. tall. The purpose of writing this thesis are: First, to determine theresponsibility of tourism entrepreneurs Bukit Selancang to the safety of touristsbased on Law Number 10 of 2009 concerning Tourism. Second, to find out theobstacles of tourism entrepreneurs in carrying out their responsibilities towardstourists in Bukit Selancang. The type of research used is empirical or sociologicallegal research, because in this paper the author conducts research at the locationor place under study in order to provide a complete and clear picture of the problemunder study. The data sources used are primary data and secondary dataThis research was conducted in Bukit Selancang, Aur Cina Village,Indragiri Hulu Regency. The population and sample in this study were SelancangHill tourists and selancang hill tourism entrepreneurs, and the sources used weresecondary data and primary data. Data collection techniques by means ofinterviews and the data obtained were then analyzed qualitatively. The conclusionthat can be drawn from the results of the First Research, because it refers to severalcases that occurred such as tourists being injured due to inadequate facilities, lossof goods in the form of helmets, in this case the tourism entrepreneur is notresponsible for the losses suffered. by tourists. All these losses must be borne by thetourism entrepreneur Bukit Selancang. Second, the constraining factors that affectthe legal responsibility of Bukit Selancang tourism entrepreneurs in Aur CinaVillage for accidents or losses experienced by tourists are the lack of publicawareness, inadequate facilities or infrastructure and weak supervision from thegovernment.Keywords : Responsibility, Tourism Entrepreneurs, Tourist safety